Active Mobility: A study on Walkability in the city of Blumenau/SC - Pereira, Edilson; Dias, Vera Lúcia Nehls (National Journal of City Management, 2022)
This research addresses aspects related to active urban mobility focusing on the understanding of walkability and the criteria that condition it. Walkability is a preponderant factor in the quality of urban space, as it is about the characteristics and conditions that a place presents for walking. In this context, this research carried out an analysis of walkability in four urban space clippings of the city of Blumenau/SC. A method for evaluating the walkability was applied, and thus the indexes for each area were identified; furthermore, interviews were carried out through a questionnaire with the objective of knowing the profile of the walker, his/her characteristics and perceptions. Thus, it could be concluded that the walkability in the researched areas shows a direct relationship between the attractiveness of the space, either by the safety conditions in all senses, by points of attraction, such as shops and services or outdoor living areas, or even by a pleasant sightseeing, added to the conditions of urban infrastructure of the sidewalks, much more than just the characteristics of the rugged terrain.